Effect of Visual Merchandising, Store Atmosphere, and Price Discount on Impulse Buying with Positive Emotion as Intervening Variable: Pengaruh Visual Merchandising, Store Atmosphere, dan Price Discount terhadap Impulse Buying dengan Positive Emotion sebagai Variabel Intervening - Raden Hanif Arga Suryana; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of Visual Merchandising, Store Atmosphere, and Price Discount on Impulse Buying with Positive Emotion as an Intervening Variable at Ace Hardware Sidoarjo. The sample used is 100 respondents. Samples were taken by purposive sampling method. The data analysis technique used is PLS-SEM analysis with the SmartPLS 3.0 program. The results of this study indicate that visual merchandising has an effect on impulse buying, store atmosphere has an effect on impulse buying, price discounts have no effect on impulse buying, visual merchandising has an effect on positive emotion, store atmosphere has an effect on positive emotion, price discount has an effect on positive emotion, positive emotion affects impulse buying, visual merchandising affects impulse buying through positive emotion, store atmosphere affects impulse buying through positive emotion, and price discounts affect impulse buying through positive emotion.